Urgensi Demokrasi Deliberatif bagi Kepemimpinan Nasional - Gusti A. B. Menoh (Yayasan Bina Darma, 2015)
This writing aims to showing the urgency of deliberative democration for leadership in Indonesian country, especially in the area of nation state (also religiousity). The political philosophy of Jurgen Habermas is urgent because after organizing the democracy for many years, Indonesia didn't make progress precisely setback on implementation of democracy . Deliberative democracy is a theory that recognize rational deliberation (discourse) between the citizen as the resource of legitimation of politically . In practice, deliberative democration, require the state (the leader: executive, judicative, and legislative) no longer lays down the law and political decision in spledid isolation, but always open to voice that arise from public over many media an organization that vocally and in civil society who played in6luence over politics system (the leader: executive, judicative, and legislative). Habermas said that deliberative politic get the power of legitimation from structure of opinion discursive and the formation of will that able to full6ill of its integration function as social only because citizen hope that the result have a rational quality. If deliberation democracy to be a reference of national leadership, so that the dreams to realized the strong and welfare of national state otomatically was real. In other word, the leadership problem that we feel right now as the heritage for along time years of feodal leadership, top down, otoritarian, not responsible, must be left . On the contrary, the leadership must wise up that their leadership resource, are the citizen so must be always open the communication sphere with and responsible to them. Keywords: Jrgen Habermas, deliberative democration, public sphere, politic, national leadership, church leadership, Indonesia.